Management problems of rapid urbanisation in Nigeria : the challenge to government and local authorities, report - Adedeji, Adebayo; Rowland, L.; Ahmadu Bello University (Ile-Ife, Nigeria : Published for the Institute of Administration [by] University of Ife Press, 1973)
This is a proceedings of a national conference on local governments held in Nigeria 1969, attended by the representatives of the 12 states. The conference examined the functions and structure of local authorities; the role of local government in planning and development; the relationship between states and local governments; the role of the government field administration in relation to local government; and inter-state cooperation in local government matters.
Includes bibliographical references.
lje 16/05/2018, ijb 11/02/2019
Loans
Keywords: Urbanisation; City planning